Teknik, Mekanisme dan Model Penilaian Kinerja Aparatur Pemerintah - Ratminto Ratminto (Centre for Public Policy and Management Studies, 2005)
Evaluation is important to improve the performance of both state apparatus and government agencies. Within government secor in Indonesia, DP 3 is applied as a tool to evaluate the performance of government apparatuses regardless its weaknesses. Efforts have been made to develop better instruments. Performance evaluation model of STPDN, BKD of Central Java Province and that of the State Minister for The empowerment of State Apparatus are part of effort. This article analysis the characteristics of the models.Kata kunci: penilaian kinerja, aparatur pemerintah, penilai